2019
DOI: 10.1002/cam4.1973
|View full text |Cite
|
Sign up to set email alerts
|

Serum level of soluble interleukin‐2 receptor is positively correlated with metabolic tumor volume on 18F‐FDG PET/CT in newly diagnosed patients with diffuse large B‐cell lymphoma

Abstract: Diffuse large B‐cell lymphoma (DLBCL) is the most frequent subtype of non‐Hodgkin lymphoma. High total metabolic tumor volume (TMTV) calculated using 18F‐FDG PET/CT images at diagnosis predicts poor prognosis of patients with DLBCL. However, high cost and poor access to the imaging facilities hamper wider use of 18F‐FDG PET/CT. In order to explore a surrogate marker for TMTV, we evaluated the correlation between the serum levels of soluble interleukin‐2 receptor (sIL‐2R) and TMTV in 64 patients with DLBCL, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…We carried out sensitivity analyses to minimize or avoid immortal time bias and to address the concern of per protocol set analysis by the time-dependent Cox regression analysis and the interim analysis with sIL-2R, respectively. 10,11 These sensitivity analyses, while important and supportive, cannot definitively address potential bias arising from the immortal bias and per protocol set analysis. However, when considering the effect of residual bias on the results, the primary finding from our study that prognosis was no better with eight cycles of (R-) CHOP or THP-COP-21 than with six cycles was consistent across the sensitivity analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We carried out sensitivity analyses to minimize or avoid immortal time bias and to address the concern of per protocol set analysis by the time-dependent Cox regression analysis and the interim analysis with sIL-2R, respectively. 10,11 These sensitivity analyses, while important and supportive, cannot definitively address potential bias arising from the immortal bias and per protocol set analysis. However, when considering the effect of residual bias on the results, the primary finding from our study that prognosis was no better with eight cycles of (R-) CHOP or THP-COP-21 than with six cycles was consistent across the sensitivity analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Histologic diagnoses were made according to the Revised European American Lymphoma classification and the World Health Organization classification. 8 , 9 Patient age, sex, anthropometric data (height and weight), performance status (PS), number of extranodal sites, stage, elevated lactate dehydrogenase, serum albumin (Alb), serum soluble interleukin-2 receptor (sIL-2R), 10 , 11 International Prognostic Index (IPI), B symptoms (fevers, night sweats, or unintentional weight loss), and bulky mass (diameter >7.5 cm) were collected as baseline demographic data. 12 , 13 Comorbidity and nutrition status at diagnosis were assessed by the Charlson Comorbidity Index (CCI) and Geriatric Nutritional Risk Index (GNRI).…”
Section: Methodsmentioning
confidence: 99%
“…We retrospectively analyzed the prognostic values of MH on baseline 18 FDG-PET/CT in 2 independent cohorts; this was the same population that we used in a previous study to explore the prognostic values of TMTV and sIL-2R. 4 In brief, the training cohort consisted of 86 newly diagnosed DLBCL patients treated at Sapporo Hokuyu Hospital between 2008 and 2013. The validation cohort included 64 patients treated at Aiiku Hospital between 2008 and 2014.…”
Section: Patientsmentioning
confidence: 99%
“…We previously reported that baseline total metabolic tumor volume (TMTV) on baseline 18 FDG-PET/CT was positively correlated with the serum level of soluble interleukin-2 receptor (sIL-2R), and TMTV and sIL-2R were useful prognostic biomarkers in newly diagnosed DLBCL. 4 High metabolic heterogeneity (MH) on 18 FDG-PET/CT is the index of heterogeneity of intratumoral 18 F-fluorodeoxyglucose uptake distribution, and it is associated with worse prognosis for various tumors. 5 Recently, high MH on the baseline 18 FDG-PET/CT image has been shown to predict worse prognosis of primary mediastinal B-cell lymphoma.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has reported evidence of the ability of volumetric indices to predict prognosis [ 36 ]. Although the volumetric indices are very useful, they are rarely mentioned in daily radiology reports because there is no consensus on how to determine the tumour boundary.…”
Section: Basic Concepts For Quantitative Fdg Pet Assessmentmentioning
confidence: 99%